2022
DOI: 10.1021/acsenergylett.2c01960
|View full text |Cite
|
Sign up to set email alerts
|

Alloying Strategy for High-Performance Zinc Metal Anodes

Abstract: Owing to the advantages of low cost, high energy density, and environment friendly, aqueous zinc ion batteries (AZIBs) are considered as promising energy storage devices. Inevitable zinc dendrites, corrosion, passivation, and hydrogen evolution reactions of zinc anodes have seriously hampered the practical application of AZIBs. To address the above-mentioned issues, zinc anode alloying is proposed as an emerging modification strategy. Therefore, it is essential to systematically summarize the obtained research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 106 publications
0
51
0
Order By: Relevance
“…In fact, the separator modification is also an effective approach to improve Zn anode stability and extend AZIBs service life, but it does not receive considerable attention to investigate separator–electrolyte or separator–anode interfaces. Filter paper, glass fiber, and polypropylene membrane separators now are the most widely used for research on AZIBs. Unfortunately, owing to the poor mechanical properties, low wettability, and tangled pore distribution, Zn dendrite formation and growth are easily arisen in these separators and cause short-circuit, which are unable to satisfy the AZIBs commercialization. Therefore, rationally designing a separator with low cost, good mechanical strength, and simple preparation to restrain the formation of Zn dendrite and water-induced side reactions is urgently needed for the development of high-performance AZIBs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the separator modification is also an effective approach to improve Zn anode stability and extend AZIBs service life, but it does not receive considerable attention to investigate separator–electrolyte or separator–anode interfaces. Filter paper, glass fiber, and polypropylene membrane separators now are the most widely used for research on AZIBs. Unfortunately, owing to the poor mechanical properties, low wettability, and tangled pore distribution, Zn dendrite formation and growth are easily arisen in these separators and cause short-circuit, which are unable to satisfy the AZIBs commercialization. Therefore, rationally designing a separator with low cost, good mechanical strength, and simple preparation to restrain the formation of Zn dendrite and water-induced side reactions is urgently needed for the development of high-performance AZIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one class of Zn plating regulation strategy has gained attention by constructing Zn-alloying sites on the Zn plating surface, where the Zn electrodeposition was effectively regulated by alloying Zn with Au, Ag, , Al, etc. The general principle of this strategy is based on the elimination of a heterogeneous Zn nucleation barrier by the high solid solubility between Zn and Zn-alloying metal and the homogenization of Zn deposition via the fast internal diffusion of Zn through the developed alloy phases.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this problem, introducing a zincophilic and chemically stable interfacial layer on the host surface is a simple approach to improve the deposition quality of Zn. 18 Zn−Me alloys 27 have been considered as promising Zn metal anodes, such as the Ag seeds can in situ alloy with metallic Zn during the initial Zn plating and then form Zn−Ag alloys to serve as Zn-ion nucleation sites. 28−30 In the same way, Zn−Cu alloys 30,31 have also been successfully prepared; as an example, Kwon et al 31 reported a Zn electroplating strategy to construct a stable CuZn 4 alloy-modified Cu foil by in situ alloying with a proper Zn loading for high energy ZIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Zn–Me alloys have been considered as promising Zn metal anodes, such as the Ag seeds can in situ alloy with metallic Zn during the initial Zn plating and then form Zn–Ag alloys to serve as Zn-ion nucleation sites. In the same way, Zn–Cu alloys , have also been successfully prepared; as an example, Kwon et al reported a Zn electroplating strategy to construct a stable CuZn 4 alloy-modified Cu foil by in situ alloying with a proper Zn loading for high energy ZIBs. Unfortunately, it is reported that the volumetric change of the in situ alloying process may decrease the adhesion of the alloy and the host materials, thus damaging the host interface stability. , Hence, it is necessary to develop an appropriate method that permits in situ construction of the alloy layer on host materials before the initial Zn plating.…”
Section: Introductionmentioning
confidence: 99%